Strategi Pencegahan Narkoba Terhadap Remaja - Rahmiyati Rahmiyati (UIN Antasari Banjarmasin, 2015)
The growing drug abuse in Indonesia, especially in South Kalimantan, an emergency that required the attention of all parties. The main pillars of drug prevention in the community of Muslims is to implement the teachings of Islam in earnest, because Islam forbids the consumption of drugs. In school guidance and counseling teacher's role is vital in the prevention and handling of drugs, for guidance and counseling officers have the duty and authority to control, supervise and assist students who are considered problematic.